A rare case of Pseudomonas putida ventriculitis in intensive care unit: A case report - Mokhtar, Mohammad Nizam; Azaharuddin, Izzuddin; Abdullah, Farah Hanim; Izaham, Azarinah; Abdul Rahman, Raha (Frontiers in Medicine, 2022)
Pseudomonas putida is a rare pathogen leading to nosocomial and central nervous system infections. Despite being a rare organism to cause bacteremia and its low virulence, it has the capability to evolve into multidrug resistant organisms and lead to mortality and morbidity in the intensive care setting. A 64-year-old male gardener presented with extensive acute subarachnoid hemorrhage with intraventricular extension causing hydrocephalus requiring embolization and coiling following a cerebral angiogram which showed bilateral posterior circulation aneurysm and left anterior circulation aneurysm. External ventricular drain (EVD) was inserted in view of worsening hydrocephalus. During intensive care unit (ICU) stay he was becoming more septic and a full septic workup including a cerebral spinal fluid culture taken from the indwelling catheter of the EVD and was found to be positive for a ceftazidime sensitive strain of Pseudomonas putida. Following treatment with intravenous ceftazidime for one week and a revision of the EVD on day 32 of admission, he continued to recover well improvement of his Glasgow coma scale (GCS) and septic parameters. Eventually he was able to wean off mechanical ventilation. He was discharged from ICU care to the neurosurgical ward with supplemental oxygen on day 42 of admission. It is necessary to be aware of the possibility of nosocomial Pseudomonas putida infection especially in patients with indwelling catheters and to consider the early initiation of appropriate antibiotic regimens once detected as well as strict precautions in hygiene during management of these patients to avoid further development of multi-drug resistant (MDR) strains.